Development of small and medium-sized business sector in the Republic of Bashkortostan - E. R. Mamleeva; N. V. Trofimova; M. Yu. Sazykina (Вестник Северо-Кавказского федерального университета)
Introduction. The article considers the main trends in the development of small and medium-sized businesses in the Republic of Bashkortostan for the period 2018 – 2022. Since 2020, the economy of the constituent entities of the Russian Federation has faced difficulties caused by external factors (difficult epidemiological situation, sanctions pressure, etc.). Materials and methods. To achieve this goal, the following methods were used: analysis, synthesis, comparison, generalization, graphical analysis and statistical analysis. The study is based on the analysis of data published in the Unified Register of Small and Medium-Sized Businesses, as well as official statistics of the Federal State Statistics Service for 2017–2022. Results and discussion. In the course of the study, key indicators that characterize the business activity of the small and medium-sized business sector were analyzed. They are the number of small and medium-sized businesses, the average annual number of employees, the turnover of small and mediumsized businesses, and their net financial result. Conclusion. Based on the results of the study, it can be concluded that, despite all the difficulties and negative forecasts, small and medium-sized businesses in the Republic of Bashkortostan have successfully adapted to crisis conditions: in 2022, there was a positive trend in almost all analyzed indicators.